From school writing to writing about onelsef: an analysis of written diaries of students from Youth and Adult Education - Florianopolis - 2008 (Tempo e Argumento, 2013)
In this article the main goal is to analyze two written diaries of students from a center of Youth and Adult Education (EJA Program) in Florianopolis, Brazil, in 2008. In that city EJA Program proposes a teaching methodology based on research projects that start from students’ reality and interests. The diaries analyzed in this article are instruments of course evaluation, reports prepared daily by students and answered by teachers, establishing thus dialogues through writing. By reading the diaries, one can reflect on how those evaluation tools no longer convey strictly school writing, becoming instead personal writing, constituent of identities and subjectivities, privileged sources for understanding two major historiographical related fields: History of Written Culture and History of Education. As part of History of Written Culture, great importance has been given to everyday or “ordinary” writing, which has been studied only from the last decade and is a privileged source of knowledge regarding common people’s everyday life and doings. In a complementary position, History of Education can also be studied from those sources. As part of that field, diaries express everyday life in classrooms, educational practices that are not exposed in official documents or books and textbooks. Rather, they demonstrate how educational processes are perceived through the lens of students, giving clues to the understanding of a particular school culture.
Keywords: Youth and Adult Education; EJA Program; history of written culture; history of education; school culture; everyday life